Pelaksanaan Pemungutan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) di Kota Denpasar - Anak Agung Triana Putri; Ida Ayu Putu Widiati; I Wayan Arthanaya (Warmadewa Press, 2021)
Gaining authority regarding buildings and land arises as a result of changes that cover the events and activities of individuals or legal entities as legal subjects who are given the responsibility to have rights to land and buildings by active laws and regulations. The purpose of this research is to reveal the implementation of the collection of Customs for the Acquisition of Land and Building Rights (BPHTB) for the transfer of rights in Denpasar City as well as the obstacles and and efforts to solve problems in the implementation of the collection of BPHTB. The method used is empirical legal research with a case approach. The data collection technique was carried out by field research. The sources of legal data used are primary and secondary, then the data is analyzed systematically. The results of the research reveal that the collection of BPHTB in the city of Denpasar uses an online system that has been regulated in the regulation of the mayor of Denpasar number 17 of 2016 which is contained in Article 5 by depositing the amount of payment to the BPD bank and paying taxes in the city of Denpasar, using a self-assessment system. The Denpasar City Government Regulation in determining the selling value in buying and selling transactions is based on verification and validation in contrast to the self-assessment system, the results of verification and validation often get the selling value set by the Regional Revenue Service which is much more than the actual value.